The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s1806-92902015001000005
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting beef consumption in the valley of Mexico

Abstract: -The objective of this study was to know the factors that determine the consumption of beef in the Metropolitan Area of the Valley of Mexico, using logit and probit modeling (nominal variable) with 400 surveys. The results showed that significant variables that determine the probability of purchasing beef are schooling, number of members per family, meat preference, family income, and presence of disease in the individual. The largest marginal effects on the purchase decision were provided by the income and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…According to (Perdana, Handayani, & Budiraharjo, 2013) the numbers of family members in a house can affect the beef demand, where if, the more number of family members so the higher purchased beef consumption will be, but the flavor level also had an influence to the increase of beef demand. Meanwhile, based on the international research that was done in Mexico, it was known that there was a definite connection between the consumed beef amount and number of family members, the number of family members was a siginificant factor in a household for making decision to beef purchase, three or four family members consumed more beef (Delgado & Flores, 2015).…”
Section: The Connection Between the Number Of Family Members And Beef...mentioning
confidence: 99%
“…According to (Perdana, Handayani, & Budiraharjo, 2013) the numbers of family members in a house can affect the beef demand, where if, the more number of family members so the higher purchased beef consumption will be, but the flavor level also had an influence to the increase of beef demand. Meanwhile, based on the international research that was done in Mexico, it was known that there was a definite connection between the consumed beef amount and number of family members, the number of family members was a siginificant factor in a household for making decision to beef purchase, three or four family members consumed more beef (Delgado & Flores, 2015).…”
Section: The Connection Between the Number Of Family Members And Beef...mentioning
confidence: 99%
“…En México existen pocos estudios que analizan el comportamiento de los consumidores en la selección de sus alimentos (Molina-Castillo et al, 2022;Sánchez-Vega et al, 2020;Rojas-Rivas et al, 2019;Serrano-Cruz et al, 2018;. Otros trabajos establecen los factores que influyen en el consumo de carne entre la población (Téllez et al, 2018;Téllez y Mora, 2015;Cortés et al, 2012;Téllez-Delgado et al, 2012). Por ejemplo, Téllez-Delgado et al (2012) identificaron que los ingresos influyen en la ingesta de carne de res, concluyendo que las personas con ingresos bajos y medios, prefieren los cortes que adquieren en mercados públicos.…”
Section: Estudios Sobre El Consumo De Carne En Méxicounclassified
“…Téllez y Mora (2015) analizaron que los factores que influyen en la disposición de compra de carne de res entre los consumidores son: el nivel educativo, las preferencias hacia diferentes tipos de carne, el tamaño de la familia y el ingreso familiar, destacando el nivel educativo y el tamaño de la familia como los más predictivos; y resaltan que la preferencia por la carne de cerdo o de ave disminuye la preferencia por el consumo de carne de res. Téllez et al (2018) amplían la investigación descrita anteriormente, pero hacia la ingesta de carne de cerdo, estableciendo que el nivel de ingreso por familia, así como la presencia de alguna enfermedad en los miembros de aquélla limitan su preferencia, ya que se asocia a múltiples enfermedades.…”
Section: Estudios Sobre El Consumo De Carne En Méxicounclassified
“…Burnier et al (2021), however, focused on not only beef intrinsic attributes such as tenderness, freshness and leanness but also experience appearance and taste for consumer choices. Delgado and Flores (2015) also reported that the demographic factors affecting consumers' meat consumption amount linked with family size and income, schooling rate, read meat types with fat contents, nutritional values and chronic diseases. Wang et al (2022), Harguess et al (2020), Tosun and Hatirli (2009), and Gündüz et al (2006 highlighted that the sensory quality attributes such as freshness, juiciness, color, flavor and quality of red meat provided a positive motivation on consumers' consumption satisfaction; when demographic factors covering families' income, food prices, their education levels, distance to market, their purchase frequencies, market club card membership and usage affected positively their red meat consumption.…”
Section: Literature Reviewmentioning
confidence: 99%